FLOOR QUANTIFICATION OF FUEL ON THE FOREST IN THE SEMIARID REGION OF PARAIBA, BRAZIL - Terezinha de Oliveira Ribeiro; Patrícia Carneiro Souto; Bruna Vieira de Souza; Jacob Silva Souto; Patricio Borges Maracaja (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
Knowing the type and amount of combustible material in the forest floor is essential for the estimation of parameters related to fire behavior. The main objectives was developed in an area of Caatinga in the Private Natural Reserve of National Patrimony owned by belonging to “Tamanduá Farm”, located in Santa Terezinha municipality,  Paraiba State, Brazil, to quantify the fuel in the forest floor. Samples were collected from October to December/2009 demarcated into seven transects in the Reserve. With the aid of a template was demarcated portion of 1.0 m x 1.0 m which was collected combustible material, living and dead, which was weighed to determine wet weight and then oven-dried to obtain dry weight. All material was further separated into leafy and non-leafy to determine the share of each class in the composition of combustible material. Moreover, there was the burning of all combustible material collected in each transect to assess the speed of propagation, the burning time and percentage burned. The greatest amount of combustible material was obtained in November with 535.3 g m2. In relation to the physiological state of the plant residue, the largest contribution to the formation of combustible material was dead